Strengthening The Sense of Patriotism in Madrasah Ibtidaiyah, Indonesia Based on The Islamic Boarding School System - Arif, Muhamad; Abd Aziz, Mohd Kasturi Nor bin; Harun, Makmur; Ma`arif, Muhammad Anas (Pascasarjana Universitas KH. Abdul Chalim, 2023)
This is a new study that shows how the process of strengthening patriotism in Madrasah Ibtidaiyah, based on Pondok Pesantren Al-Azhar Menganti Gresik, is being carried out. The significance of this study can be seen in various issues concerning patriotism education for good citizens in countries such as Singapore, Japan, and Belgium. The researcher used a qualitative research method with a case study approach, in-depth interviews, and comprehensive analysis through condensation data, data display, and conclusions to arrive at the conclusion that Madrasah Ibtidaiyah's process of strengthening patriotism can shape students' personalities through several programmes. Parents and the madrasah worked together. According to Albert Bandura's triadic reciprocal determinism social learning theory, all elements play a reciprocal role in the process of strengthening the patriotism personality in students.